Epithelial Regnase-1 inhibits colorectal tumor growth by regulating IL-17 signaling via degradation of NFKBIZ mRNA - Eriko Iguchi; Atsushi Takai; Natsumi Oe; Yosuke Fujii; Mayuki Omatsu; Haruhiko Takeda; Takahiro Shimizu; Takahisa Maruno; Yuki Nakanishi; Masanori Yoshinaga; Takashi Maruyama; Hiroyuki Marusawa; et al. (Proceedings of the National Academy of Sciences, 2025)
Regnase-1 is a ribonuclease that regulates inflammation in immune cells by degrading cytokine mRNA. Regnase-1 was identified as one of the frequently mutated genes in the inflamed colorectal epithelium of patients with ulcerative colitis; however, its significance in intestinal epithelial cells during the tumorigenic process remains unknown. Therefore, we developed an Apc Min/+ mouse model lacking Regnase-1 in intestinal epithelia. Regnase-1 deletion significantly enhanced colon tumor growth accompanied by elevated levels of extracellular signal-regulated kinase (ERK) phosphorylation in tumor tissues. Transcriptome analysis of the tumor tissues revealed that Nfkbiz , a mediator of the interleukin (IL)-17 signaling pathway, was the primary degradative target of Regnase-1 in enterocytes and that Regnase-1 deficiency enhanced IL-17 signaling. The treatment with antibiotics or IL-17-neutralizing antibody canceled the proliferative effect of colon tumors due to Regnase-1 deletion, suggesting the protective role of Regnase-1 against colon tumor growth was dependent on IL-17 signaling triggered by gut microbes. Analysis of the Nfkbiz knockout mouse model demonstrated that the tumor-suppressive effect of Regnase-1 depended on Nfkbiz expression. Remarkably, oral treatment of dimethyl fumarate, a potential inhibitor of Regnase-1 protein inactivation, suppressed tumor growth, downregulated Nfkbiz , and suppressed ERK activation. Furthermore, TCGA data analysis revealed that low Regnase-1 expression in colorectal cancer tissue was related to poor prognosis. Therefore, Regnase-1 represses colon tumor growth by regulating IL-17 signaling via Nfkbiz mRNA degradation. Regnase-1 could be a potential therapeutic target in colon tumors.